REDESAIN KURSI BAMBOO BENT LAMINATION DENGAN KONSEP DESIGN GUIDELINES COLLABORATIVE FRAMEWORK (DGLS-CF) MENUJU SUSTAINABLE PRODUCT - Pranindo, Arya; Nurkertamanda, Denny (Universitas Muhammadiyah Surakarta, 2013)
Bamboo laminate is a product made from bamboo slats, which are glued parallely to the fibers. The adhesion results can be either board or beam thickness depending on the size and width. Bamboo has a high strength layer against abrasion and bending moment. In the previous study, lamination bamboo chair has the disadvantage on high production costs and a long process. Thus, it needs for redesigning seats from previous research. Design method with the concept of Design Guidelines Collaborative Framework is expected to make a product that is produced sustainably chair and have a relatively affordable cost of production. This chair design is made by bamboo bent lamination and bending process is done with Tohnet method with existing technology, that will generate power for the same structure with wood for the furniture industry and can not be separated from the value of comfort (ergonomic), aesthetic values and also not rule out environmental aspects according to Indonesian National Standard.